2004
DOI: 10.1161/01.cir.0000144462.08345.b9
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-Restricted Overexpression of Human Endothelin-1 Causes Vascular Remodeling and Endothelial Dysfunction

Abstract: Background-Endothelin (ET)-1 is a potent vasoconstrictor that contributes to vascular remodeling in hypertension and other cardiovascular diseases. Endogenous ET-1 is produced predominantly by vascular endothelial cells. To directly test the role of endothelium-derived ET-1 in cardiovascular pathophysiology, we specifically targeted expression of the human preproET-1 gene to the endothelium by using the Tie-2 promoter in C57BL/6 mice. Methods and Results-Ten-week-old male C57BL/6 transgenic (TG) and nontransge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
236
4
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(260 citation statements)
references
References 46 publications
11
236
4
9
Order By: Relevance
“…11 This points to a transient upregulation of the endothelin system during the development of hypertension. ET-1 is not only a very potent vasoconstrictor 12 but is also a proinflammatory agent, 15 has mitogenic effects on vascular smooth muscle cells, 13 is pro-angiogenic, 16 pro-oxidant 33 and promotes fibrosis. 14 Moreover, endothelium restricted overexpression of ET-1 causes vascular remodeling and endothelial dysfunction in the absence of a hemodynamic effect.…”
Section: Discussionmentioning
confidence: 99%
“…11 This points to a transient upregulation of the endothelin system during the development of hypertension. ET-1 is not only a very potent vasoconstrictor 12 but is also a proinflammatory agent, 15 has mitogenic effects on vascular smooth muscle cells, 13 is pro-angiogenic, 16 pro-oxidant 33 and promotes fibrosis. 14 Moreover, endothelium restricted overexpression of ET-1 causes vascular remodeling and endothelial dysfunction in the absence of a hemodynamic effect.…”
Section: Discussionmentioning
confidence: 99%
“…ET-1 increases oxidative stress through the activation of NAD(P)H oxidase-a key enzymatic source for superoxide anion in the vascular wall. 12,13,16,27 Excessive oxidative stress activates several redox-sensitive signalling pathways resulted in activation of MAP kinase family, tyrosine kinases, transcription factors nuclear factor kB, activator protein-1, vascular cellular adhesion molecule-1 and increase release of proinflammatory cytokines. 8,13,26,28,29 The contribution of ET-1, NAD(P)H oxidase and reactive oxygen species in VSMC proliferation was confirmed by the possibility of blocking this process by pre-incubation of VSMC with ET A receptor antagonist, 13 NAD(P)H oxidase inhibitor 12,16 or with antioxidants; 12,13,16 however, it was documented for extracellular superoxide dismutase, 13 and among the antioxidants included in FRAP for ascorbic acid.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,16,27 Excessive oxidative stress activates several redox-sensitive signalling pathways resulted in activation of MAP kinase family, tyrosine kinases, transcription factors nuclear factor kB, activator protein-1, vascular cellular adhesion molecule-1 and increase release of proinflammatory cytokines. 8,13,26,28,29 The contribution of ET-1, NAD(P)H oxidase and reactive oxygen species in VSMC proliferation was confirmed by the possibility of blocking this process by pre-incubation of VSMC with ET A receptor antagonist, 13 NAD(P)H oxidase inhibitor 12,16 or with antioxidants; 12,13,16 however, it was documented for extracellular superoxide dismutase, 13 and among the antioxidants included in FRAP for ascorbic acid. 12,16 It was also shown that vitamin C inhibited activation of mitogen-activated protein kinase and VSMC proliferation in cultured rat aortic smooth muscle cells, 26 and in an in vivo experiment it was demonstrated that vitamin C supplementation decreased activation of NADPH oxidase and superoxide anion generation, prevented vascular hypertrophy and increased plasma total antioxidant status and superoxide dismutase in arterial wall in stroke-prone spontaneously hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations